Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1101/2022.06.13.495865
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative immune responses toMycobacterium tuberculosisin people with latent infection or sterilizing protection

Abstract: Tuberculosis (TB) affects 2 billion people worldwide and causes 1.5 million deaths every year. There is great need for new TB vaccines that are more efficacious than the currently licensed BCG vaccine, which provides only limited protection. Our goal was to identify potential targets for new TB vaccines by characterizing the immune responses that distinguish individuals with sterilizing protection against TB (TB-resisters), defined by presence of TB-specific immune responses and absence of latent infection, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Flynn's team recently demonstrated that CD8 + T‐cell depletion leads to the dissemination of Mtb in monkeys and an increase in lung inflammation, indicating the necessity of CD8 + T cells for protection during early Mtb infection (Winchell et al, 2023). Similarly, a study found that LTBI patients have more iNKT CD8 + T cells, while TB‐Resister individuals have a subgroup of CD8 + GMM + GranzB + T cells that may be associated with their strong resistance (Jalbert et al, 2023). The underestimated anti‐TB function of CD8 + T cells may be related to the infective dose employed in animal models.…”
Section: Immuno‐cytological Characteristics Of Ltbi and Atbmentioning
confidence: 99%
See 2 more Smart Citations
“…Flynn's team recently demonstrated that CD8 + T‐cell depletion leads to the dissemination of Mtb in monkeys and an increase in lung inflammation, indicating the necessity of CD8 + T cells for protection during early Mtb infection (Winchell et al, 2023). Similarly, a study found that LTBI patients have more iNKT CD8 + T cells, while TB‐Resister individuals have a subgroup of CD8 + GMM + GranzB + T cells that may be associated with their strong resistance (Jalbert et al, 2023). The underestimated anti‐TB function of CD8 + T cells may be related to the infective dose employed in animal models.…”
Section: Immuno‐cytological Characteristics Of Ltbi and Atbmentioning
confidence: 99%
“…Later that year, this discovery was confirmed in animal models by the research teams led by Steven Porcelli and Samuel Behar (Im et al, 2008; Sada‐Ovalle et al, 2008). A recent community survey in LTBI individuals and TB‐Resisters revealed that the frequency of iNKT cells in TB‐Resisters is higher than in LTBI individuals, suggesting that iNKT cells may contribute to clearing the infectious agent before the establishment of latency (Jalbert et al, 2023).…”
Section: Immuno‐cytological Characteristics Of Ltbi and Atbmentioning
confidence: 99%
See 1 more Smart Citation